2014
DOI: 10.1186/1471-2466-14-82
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soluble and cellular inflammatory markers in nasal lavage obtained from Cystic Fibrosis patients during intravenous antibiotic treatment

Abstract: BackgroundIn cystic fibrosis (CF) patients, the upper airways display the same ion channel defect as evident in the lungs, resulting in chronic inflammation and infection. Recognition of the sinonasal area as a site of first and persistent infection with pathogens, such as Pseudomonas aeruginosa, reinforces the “one-airway” hypothesis. Therefore, we assessed the effect of systemic antibiotics against pulmonary pathogens on sinonasal inflammation.MethodsNasal lavage fluid (NLF) from 17 CF patients was longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 50 publications
3
16
1
Order By: Relevance
“…Comparative studies of cultures isolated from both the upper and lower airways of patients with CF have shown genotypic and phenotypic similarity between P. aeruginosa grown from sinus, sputum or endotracheal cultures, particularly in terms of bacterial type, strain and antibiotic resistance patterns in patients >8 years of age . In agreement with the descending infection hypothesis, the use of nasal lavage as a potential diagnostic tool to monitor the airways in patients with CF has been suggested by several studies …”
Section: Resultsmentioning
confidence: 66%
“…Comparative studies of cultures isolated from both the upper and lower airways of patients with CF have shown genotypic and phenotypic similarity between P. aeruginosa grown from sinus, sputum or endotracheal cultures, particularly in terms of bacterial type, strain and antibiotic resistance patterns in patients >8 years of age . In agreement with the descending infection hypothesis, the use of nasal lavage as a potential diagnostic tool to monitor the airways in patients with CF has been suggested by several studies …”
Section: Resultsmentioning
confidence: 66%
“…Non‐invasively collected nasal lavages (NL) from the patient's UAW bear the potential not only to monitor airway colonization but also to assess host defense and inflammation. In this regard, we showed that concentrations of soluble inflammation markers in UAW sampled by NL are linked to disease severity and to the colonization status . For instance, we demonstrated that a range of soluble pro‐inflammatory and neutrophil‐related mediators, among them IL‐1β, IL‐6, and IL‐8, are more frequently detected in NL of CF patients than in NL of healthy controls .…”
Section: Introductionmentioning
confidence: 81%
“…Inflammation in CF is characterized by high intraluminal IL 8 levels and high concentrations of polymorphonuclear cells [240]. The inflammatory response of the airway in COPD patients is likely more complex [241].…”
Section: The Differences Between Chronic Bronchitis and Cystic Fibrosismentioning
confidence: 99%